Physicochemical and antioxidant properties of pomelo residues using different drying methods and kinetic models of naringin degradation - Abd Rahman, Nur Farhana (2020)
Tambun Pomelo (PO52) also known as Limau Bali in Malaysia is a native citrus fruit recognized as the largest citrus fruit in the world. Pomelo is commonly eaten fresh while the pomelo residues (~50%) consist of flavedo, albedo, lamella and pulp waste discarded without acknowledging its potential. A significant amount (p < 0.05) of antioxidant compounds was found in the pomelo residues compared to the pomelo flesh. One of the major antioxidant compounds namely naringin in pomelo peel was stated as a health-promoting compound with the ability to lower the risk of heart disease. However, high levels of moisture from fresh pomelo residues cause it to deteriorate over time, because of the microorganism reactions. Thus, the drying process was recommended as a method of preservation. Conventional hot air oven drying (CD) is known using hot air as a heat source for drying a product while the mechanism of vacuum oven drying (VD) utilized the removal of water molecules by evaporation due to the reduced pressure. However, optimum drying methods or conditions have yet to be investigated. Furthermore, the determination of drying kinetics of conventional drying (CD) and vacuum drying (VD) which, explain the drying behavior of pomelo residues at different drying temperatures has not yet been established. Information on the degradation of the kinetic constant of naringin and its antioxidant capacities in pomelo residue during storage is also limited. Therefore, the overall aims of this research were to investigate the impact of different drying methods (CD and VD) on the quality of pomelo residues. The selection of optimum drying parameters was based on the capability to retain high total phenolic content (TPC) and contribute to antioxidant capacity (DPPH scavenging activity), where high desirability index (D ≥ 0.80) were obtained from statistical analysis. Furthermore, kinetic modeling was analyzed for both drying methods and degradation of naringin in dried pomelo residues during storage were also identified. Selection of best drying models was referred to the highest value of determination of coefficient (R2) and the lowest value of standard error of estimates (SEE) between drying models. The effects of storage time (12th week at 8̂ °C) for both drying methods applied were also compared and the fitness of kinetic degradation of naringin and antioxidant capacities to zero, first and second order was evaluated. The results showed that both drying methods (CD and VD) at different drying temperature significantly affected (p < 0.05) the quality of the pomelo residues. Pomelo albedo was found to contain the highest total phenolic content when compared to other pomelo residues. The current findings also showed that VD at 90 °C (VD90) was indicated as the best drying process for pomelo albedo (D ≥ 0.80). The diffusion approach model showed the best fit for CD whereas the two-term exponential model showed the best fit for VD method of pomelo albedo at 50 - 90 °C of drying temperatures. The effective moisture diffusivity (Deff) was shown to decrease linearly over the stated temperature range - from 5.00 x 10-7 to 6.98 x 10-7 m2/s for CD whereas Deff for VD was shown to increase -within the range of 9.86 x 10-7 - 1.30 x 10-6 m2/s. The absence of oxygen was shown to be correlated with the rate of moisture that evaporated from samples to the environment under vacuum condition in VD drying process (p < 0.05). During storage, vacuum dried crude extract (VC) attributed to a higher concentration of naringin when compared to freeze-dried crude extract (FC) at the initial week (0th week)(p < 0.05), however, as storage time increases, the rate of naringin degradation kinetic were found to be lower in FC (p < 0.05), indicating higher stability of FC than VC. Naringin degradation can be described in zero, first and second order with the highest value (R2 > 0.89) and lowest value of SEE (value less than 0.05). The present study provides insightful information for the post-harvest research, food, nutraceutical, and pharmaceutical industry as a guideline to produce a new alternative source of higher bioactive compounds from pomelo’s albedo.